SISTEM PERIJINAN PERDAGANGAN MAKANAN RINGAN TANPA LABEL MELALUI PLATFORM BELANJA ONLINE - Erlis Kurnia Parmasari; Dipo Wahjoeno (Gapenas Publisher, 2022)
This study aims to seek and find legal certainty regarding the flow of the labelless snack trade licensing system through an online shopping platform in the city of Surabaya. This research uses normative research methods, namely research that examines the study of documents and archives, using secondary data such as legal theory, statutory provisions, and opinions from undergraduate graduates. This research was conducted by analyzing the principles, theories and legal concepts as well as statutory provisions related to the online licensing system in terms of trading of unlabeled snacks through online shopping platforms. The problem in this research is that there are still many unlabeled snacks that have the potential to harm consumers. The researcher uses a concept that has been designed in such a way as to find legal certainty regarding the management of a labelless snack trade licensing system, in which in this case the rights of consumers are not fulfilled and the obligations of business actors are not carried out properly and correctly